Efektivitas Lidokain Intravena Kontinyu Perioperatif Terhadap Intensitas Nyeri Dan Total Konsumsi Opioid Pasca Bedah Dekompresi Dan Stabilisasi Posterior Vertebra - Fadli Rachman; Ratnawati R; Andi Muhammad Takdir Musba (Faculty of Medicine, Hasanuddin University., 2020)
introduction: Intravenous lidocaine had been used as multimodal analgesia strategy in treating acute postoperative pain. This study aimed to examine the effectivity of perioperative intravenous lidocaine infusion on pain intensity and total opioid requirements postoperative. Methods: This study was a double blind randomized control trial on ASA physical status I-II, aged 18-60, BMI 18-30 kg/m2 underwent to spine decompression and stabilisation surgery in Wahidin Sudirohusodo general hosputal, Makassar. Results: The samples were randomly devided into lidocaine group ( n=28) received lidocaine 1,5 mg/kg before intubation, followed by 1,5 mg/kg/hour intraoperative and 1 mg/kg/hour untl 12 hour postoperative, and the control group (n=28) received placebo NaCl 0,9%. The data were analyzed with Chi-square test, independent-t test, and Mann-Whitney test, and considered significant if the p value <0,05. The study result showed that compared to the control group, the pain intensity of lidocaine group were lower in measurement time 6 (p=0,05),12 (p=0,045) and 24 (p=0,031) hour postoperative but not in 2 (p=148) and 4 (p=0,472) hour postoperative. Total fentanyl consumption 24 hour postoperative were lower in lidocaine group ( 418,32±146,45 vs 579,86±145,29 ; p=0,000). Conclusions: This study concluded that administration of intravenous lidocaine infusion perioperative able to reduce pain intensity dan total opioid requirements after spine decompression and stabilisation surgery.